Crystal structure of cytoplasmic acetoacetyl‐CoA thiolase from Saccharomyces cerevisiae. Issue 1 (26th January 2018) - Zhou, Pengfei; Zhu, Zhongliang; Hidayatullah Khan, Muhammad; Zheng, Peiyi; Teng, Maikun; Niu, Liwen
Abstract : Structural comparison of the apo structure of S. cerevisiae thiolase with the structure of the CoA‐bound complex of human mitochondrial acetoacetyl‐CoA thiolase raises the alternate hypothesis that its identical ordered conformation is induced by substrate binding. Abstract : Thiolases are vital enzymes which participate in both degradative and biosynthetic pathways. Biosynthetic thiolases catalyze carbon–carbon bond formation by a Claisen condensation reaction. The cytoplasmic acetoacetyl‐CoA thiolase from Saccharomyces cerevisiae, ERG10, catalyses carbon–carbon bond formation in the mevalonate pathway. The structure of a S. cerevisiae biosynthetic thiolase has not previously been reported. Here, crystal structures of apo ERG10 and its Cys91Ala variant were solved at resolutions of 2.2 and 1.95 Å, respectively. The structure determined shows that ERG10 shares the characteristic thiolase superfamily fold, with a similar active‐site architecture to those of type II thiolases and a similar binding pocket, apart from Ala159 at the entrance to the pantetheine‐binding cavity, which appears to be a determinant of the poor binding ability of the substrate. Moreover, comparative binding‐pocket analysis of molecule B in the asymmetric unit of the apo structure with that of the CoA‐bound complex of human mitochondrial acetoacetyl‐CoA thiolase indicates the canonical binding mode of CoA. Furthermore, the steric hindrance revealed in a structural comparison of molecule A with the CoA‐bound form raise the possibility of conformational changes that are associated with substrate binding.